Index of Productive Syntax for Children Who Speak African American English - Oetting, Janna B. (2010)
PURPOSE: The validity of the Index of Productive Syntax (IPSyn; Scarborough, 1990) for children who speak African American English (AAE) was evaluated by conducting an item analysis and a comparison of the children’s scores as a function of their maternal education level, nonmainstream dialect density, age, and clinical status. METHOD: The data were language samples from 62 children; 52 of the children were between the ages of 4 and 6 years and were classified as developing typically, and 10 were 6 years old with specific language impairment (SLI). RESULTS: All IPSyn items were produced by at least 1 child, and 88% of the items were produced by 50% or more of the children. The children’s IPSyn scores were unrelated to maternal education level and dialect density and were visually comparable to IPSyn scores reported for children who speak mainstream English. Nevertheless, IPSyn could not be used to detect differences between the 4- to 6-year-olds based on age, nor could it be used to detect differences between the 6-year-olds with and without SLI. CONCLUSION: IPSyn is a valid measure for AAE speakers, but it can be insensitive to age and clinical differences between children who are over the age of 48 months.